1987
DOI: 10.1161/01.hyp.9.6_pt_2.iii142
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and regional hemodynamic effects of calcitonin gene-related peptide.

Abstract: Calcitonin gene-related peptide, a 37-amino-acid neuropeptide, has been shown to be widely distributed in periadventitial nerves throughout the cardiovascular system, particularly in association with coronary arteries. In vivo and in vitro studies have demonstrated that calcitonin gene-related peptide possesses potent vasodilator properties. Circulating calcitonin gene-related peptide is derived primarily from periadventitial nerves, though its systemic and regional hemodynamic effects are unknown. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 13 publications
3
25
1
Order By: Relevance
“…It will therefore be necessary in future studies to determine if this mucosal vasodilatation or any mediator release is a direct effect of ET-1 in the gastric microcirculation, perhaps through activation of ETB or other ET receptors (Masaki et al, 1991) or if it occurs secondarily to microvascular injury induced by Local intra-arterial infusion of a-CGRP induced a significant increase in gastric mucosal LDF. This agrees with previous reports where a-CGRP was found to be a potent vasodilator in the gastric microcirculation, determined by use of a variety of techniques including laser Doppler flowmetry and hydrogen gas clearance (Dipette et al, 1987;Bauerfeund et al,1989;Li et al, 1991;. Intravenous infusion of a-CGRP can reverse the vasoconstrictor action of ET-1 on the internal carotid vascular bed in the rat (Gardiner et al, 1990), and local a-CGRP administration reduces the vasoconstriction induced by ET-1 in rabbit skin (Brain et al, 1988).…”
Section: Effect Of Ax-cgrp On Et-j-induced Mucosal Injurysupporting
confidence: 91%
“…It will therefore be necessary in future studies to determine if this mucosal vasodilatation or any mediator release is a direct effect of ET-1 in the gastric microcirculation, perhaps through activation of ETB or other ET receptors (Masaki et al, 1991) or if it occurs secondarily to microvascular injury induced by Local intra-arterial infusion of a-CGRP induced a significant increase in gastric mucosal LDF. This agrees with previous reports where a-CGRP was found to be a potent vasodilator in the gastric microcirculation, determined by use of a variety of techniques including laser Doppler flowmetry and hydrogen gas clearance (Dipette et al, 1987;Bauerfeund et al,1989;Li et al, 1991;. Intravenous infusion of a-CGRP can reverse the vasoconstrictor action of ET-1 on the internal carotid vascular bed in the rat (Gardiner et al, 1990), and local a-CGRP administration reduces the vasoconstriction induced by ET-1 in rabbit skin (Brain et al, 1988).…”
Section: Effect Of Ax-cgrp On Et-j-induced Mucosal Injurysupporting
confidence: 91%
“…It is likely the latter was due to a venodilator action of human a-CGRP (Tornebrandt et al, 1987;Crossman et al, 1987; but see Al-Kazwini et al, 1987;Marshall et al, 1988). The present results, therefore, provide some explanation for the conflicting data in the literature regarding the cardiac haemodynamic effects of CGRP (DiPette et al, 1987;Lappe et al, 1987;Siren & Feuerstein, 1988;Ando et al, 1990) (see Introduction), since it is apparent that the effects of the peptide depend on the dose used. Moreover, it may be that the cardiac haemodynamic responses to bolus injections of CGRP would give a less clear picture of the interrelated changes that were seen in the present study, particularly with the infusion of the higher dose of human a-CGRP.…”
Section: Discussionmentioning
confidence: 50%
“…However, results of experiments in rats are less clearcut, possibly because of limitations with the methodology used. Thus, there have been two studies (DiPette et al, 1987;Ando et al, 1990) using the radiolabelled microsphere technique in acutely prepared rats (3 h post surgery), in which single measurements of cardiac output were made at a fixed time point after bolus injections of CGRP. Using this approach DiPette et al (1987) observed a small increase, while Ando et al (1990) found no change, in cardiac output after administration of rat and human a-CGRP, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…6 ' 7 The mechanism of blood pressure reduction is by peripheral arterial dilation, which reduces total peripheral resistance. 7 In addition to its vasodilator properties, CGRP has marked positive chronotropic and inotropic effects. 8 Immunocytochemical techniques have identified CGRP-containing nerve fibers throughout the cardiovascular system, particularly in association with blood vessels 9 ; the coronary circulation appears to be especially sensitive to the vasodilator effects of CGRP.…”
Section: Calcitonin Gene-related Peptide Gene Expression In the Spontmentioning
confidence: 99%